Chemical heterogeneity among cloud drop populations and its influence on aerosol processing in winter clouds - Xu, Gang, author; Collett, Jeffrey L., Jr., author (Colorado State University. Libraries, 1998)
Drop-size resolved measurements of winter cloud composition in the Rocky mountains of northern Colorado revealed significant variations of cloud drop pH, ion (SO/, N03-, NH/, Ca2+) concentrations, and concentrations of trace metal catalysts (Fe and Mn) with drop size. The observed chemical heterogeneity across the cloud drop size spectrum was used to evaluate its influence on rates of in-cloud sulfate production and scavenging of major inorganic aerosol components by precipitation. The findings indicates that the size-dependent chemical composition of clouds tends to enhance aqueous sulfate production rates and to reduce the efficiency with which accumulation mode aerosol species are scavenged by precipitation. Simultaneous measurements of snow chemical composition and the degree of cloud drop capture by snow crystals (riming) revealed a significant positive correlation between snow composition and the extent of ice crystal riming in two of four cases studied. In the remaining cases it was found that the variations of snow composition were significantly correlated with air mass changes. Measurements of the size spectra of cloud drops attached on the surface of snow crystals showed that 10-17 µm and >17 µm cloud drop size fractions contributed significantly to accreted drop mass; little accreted mass was associated with drops smaller than 10 µm diameter.
December 1998.
Also issued as Gang Xu's thesis (M.S.) -- Colorado State University, 1999.
Keywords: Cloud physics; Aerosols; Ice crystals